Customer Decision Factors in Choosing Savings Products: Product, Service Quality, and Religiosity: Study of Bank Muamalat Customers, Malang City - Dwi Sukma Jaya Hariadi; Khusnudin Khusnudin (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study examines the determinants affecting consumer choices about savings products at Bank Muamalat, Malang City. It examines three primary factors: product quality, service quality, and religiosity, deemed essential for recruiting and retaining consumers in the competitive Islamic banking industry. The study utilizes a quantitative methodology, applying multiple linear regression analysis to assess the impact of these variables on consumer choices. Data were gathered via standardized surveys administered to Bank Muamalat clients, resulting in the analysis of 200 valid responses. The results indicate that all three aspects substantially and positively affect customer decisions. The quality of the product is crucial, highlighting attributes such as transparency, adaptability, security, and adherence to Islamic standards. Clients like innovative savings instruments such as hajj savings and school savings, which address particular requirements while complying with Sharia principles. Service quality is the primary determinant that influences customer decisions. Clients value responsive, professional, and amicable services that embody Islamic principles. Technological innovations, like digital banking applications, augment the client experience by facilitating seamless and fast transactions. Integrating superior human service and contemporary technological solutions enhances client pleasure and loyalty. Religiosity significantly influences financial decision-making, underscoring the necessity of spiritual connection. Clients favor Bank Muamalat due to its commitment to Islamic banking principles, ensuring that their financial transactions are devoid of riba (usury), gharar (uncertainty), and maysir (gambling). This predilection, driven by religion, distinguishes Bank Muamalat from conventional banks and fortifies its standing in the Islamic banking sector. The research concludes that product quality, service quality, and religiosity jointly influence customer decisions, with service quality being the predominant determinant. These findings highlight the necessity for Islamic banks, such as Bank Muamalat, to sustain a balance between functional and spiritual dimensions in their services. Improving service quality via personnel training and technical advancements, creating Sharia-compliant goods, and strengthening the bank's religious image is essential for client attraction and retention. This study enhances the literature on Islamic banking and offers pragmatic insights for augmenting competitiveness within the sector. Subsequent research may broaden its reach by incorporating supplementary variables, such as trust or brand image, and use a mixed-methods technique to attain a more profound understanding of consumer behavior.